1996
DOI: 10.1002/(sici)1096-9861(19960617)370:1<23::aid-cne3>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the striatal neurons expressing the D1 dopamine receptor in humans

Abstract: We studied D1 dopamine receptor (D1R) gene expression in the human striatum during ontogeny by in situ hybridization, immunohistochemistry, and D1R ligand autoradiography. D1R mRNA, protein, and binding sites ([3H]SCH 23390) were detected in the striatum from week 12 of fetal life. At this time, D1R mRNA was predominant in the striosomal neurons; D1R immunoreactivity (D1R-IR) and D1R binding sites displayed a pattern similar to D1R mRNA. D1R-IR was essentially present in striosomal cell bodies and neuropil, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…We next determined whether there was a similar colocalization of SNX5 and D 1 R in the caudate nucleus and putamen of the WKY rat brain. Most of the neurons in these areas express D 1 R (30). We observed discrete localization of both D 1 R and SNX5 in the neurons found at the caudate nucleus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next determined whether there was a similar colocalization of SNX5 and D 1 R in the caudate nucleus and putamen of the WKY rat brain. Most of the neurons in these areas express D 1 R (30). We observed discrete localization of both D 1 R and SNX5 in the neurons found at the caudate nucleus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ontogeny of the human striatum has not been studied comprehensively, and, indeed, very few studies have been done. Most studies to date have focused on the fetal brain (13–40 weeks gestation) and have shown in striatum patchy distributions with striosomal enrichments of acetylcholinesterase (AChE) and muscarinic cholinergic binding sites (Nastuk and Graybiel, 1985), AChE and NADPH-diaphorase (Sajin et al, 1992), calbindin (Letinic and Kostovic, 1996), dopamine D1 receptor and dynorphin mRNA (Brana et al, 1996), glutamate receptor scaffold kinase anchoring protein (Ulfig et al, 2001), and synaptophysin (Ulfig et al, 2000). A study of postnatal human brain revealed an inversion from an immature pattern of calbindin-enriched striosomes to a mature pattern of calbindin-enriched matrix sometime between term gestation to 18 months of life (Letinic and Kostovic, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the same developmental phases occur approximately 2 days later (Altman and Bayer 1981;Voorn et al 1988). DA synthesizing neurons in the human fetal brain are also established very early in development, namely, at around 5 weeks post-conception (Pickel et al 1980;Brana et al 1996;Aubert et al 1997). Hence, the cascade of developmental events that leads to the establishment of the mesocorticolimbic and mesostriatal DA systems starts early in fetal life.…”
Section: Anatomy and Development Of The Mesocorticolimbic Da Systemmentioning
confidence: 99%